A compact broadband MMIC sub-harmonic mixer using quasi-lumped transmission lines. Issue 10 (October 2015) - Zhang, Shengzhou; Sun, Lingling; Wen, Jincai; Liu, Jun
Abstract A compact broadband monolithic microwave integrated circuit (MMIC) sub-harmonic mixer using an OMMIC 70 nm GaAs mHEMT technology is demonstrated for 60 GHz down-converter applications. The present mixer employs an anti-parallel diode pair (APDP) to fulfill a sub-harmonic mixing mechanism. Quasi-lumped components are employed to broaden the operational bandwidth and minimize the chip size to 1.5×0.77 mm2. The conversion gain is optimized by a quasi-lumped 90° phase shift stub. Experimental results show that from 50 GHz to 70 GHz, the conversion gain varies between −12.1 dB and −15.2 dB with a LO power level of 10 dBm and 1 GHz IF. The LO-to-RF, LO-to-IF and RF-to-IF isolations are found to be greater than 19.5 dB, 21.3 dB and 25.8 dB, respectively. The second harmonic component of the LO signal is suppressed. The proposed mixer has an input 1 dB compression point of -2 dBm and exhibits outstanding figure-of-merits.